Analysis of Handling Funding in Non-Insurance Emergency Patients (Case Study of Muhammadiyah Bandung Hospital) - Supriyadi Supriyadi; Adinda Salwa Fadillah (Penerbit Jurnal Indonesia, 2023)
This study aims to determine the handling of financing for non-insurance emergency patients at Muhammadiyah Bandung Hospital, to find out the problems and efforts that have been made by the hospital and the weaknesses of the efforts that have been made in handling non-insurance emergency patient financing. Researchers in this study used descriptive qualitative research method by exploring the meaning of a phenomenon that occurs by describing it through specific and scientific words and language. The results obtained in this study are in dealing with the problem of handling financing in non-insurance emergency patients, the Hospital has made efforts in accordance with procedures at Muhammadiyah Bandung Hospital. The results of this study can increase understanding and attention to financing problems in Indonesia, especially in non-insurance emergency patients. place of research, interviews with several parties involved in handling financing for non-insurance emergency patients and documenting research activities both interview activities and financing handling activities for non-insurance emergency patients